Determination of chlamydial load in recurrent miscarriage in relation to some female sex hormones: a case-control study - Ray, Ankita; Pradhan, Dibyabhaba; Arora, Renu; Siraj, Fouzia; Rastogi, Sangita (The Journal of Infection in Developing Countries, 2023)
Introduction: Chlamydia trachomatis is a frequent cause of adverse pregnancy outcomes including recurrent spontaneous abortion (RSA). However, regulation of infectious load by host immune response is unknown. Female sex hormones are known to affect C. trachomatis infection. The aim of this study was to determine correlation of chlamydial infectious load and gestational age with concentration of progesterone/estrogen in RSA. Methodology: Urine and non-heparinized blood were collected from patients with history of > 3 spontaneous abortions (n = 150, cases) and those with history of > 2 successful deliveries (n = 150, controls) from Department of Obstetrics and Gynecology, Safdarjung hospital, New Delhi, India. C. trachomatis positivity was determined by polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) and chlamydial load by real-time PCR. Estrogen and progesterone concentrations were estimated by ELISA and correlated with chlamydial load. Results: 22/150 case patients were positive for C. trachomatis. 2,000–10,000 copies/mL of chlamydial load were detected in infected RSA patients. Progesterone concentration showed significant decrease while estrogen concentration was significantly increased in C. trachomatis-positive RSA patients versus controls. Chlamydial load and estrogen concentration were positively correlated while progesterone concentration was negatively correlated with chlamydial load. Gestational age was positively correlated with concentration of estrogen and negatively correlated with concentration of progesterone in infected-RSA women. Conclusions: Overall findings suggest that interplay between chlamydial copy load, hormonal changes such as increased expression of estrogen and decreased expression of progesterone, and advanced gestational age may be contributing as deciding factors for ensuing RSA during C. trachomatis-infection.